The prospects of rubberwood biomass energy production in Malaysia - Ratnasingam, Jegatheswaran; Ramasamy, Geetha; Lim, Tau Wai; Senin, Abdul Latib; Muttiah, Neelakandan (North Carolina State University, 2015)
Rubber has been shown to be one of the most important plantation crops in Malaysia, and rubber tree biomass has widespread applications in almost all sectors of the wood products manufacturing sector. Despite its abundance, the exploitation of rubberwood biomass for energy generation is limited when compared to other available biomass such as oil palm, rice husk, cocoa, sugarcane, coconut, and other wood residues. Furthermore, the use of biomass for energy generation is still in its early stages in Malaysia, a nation still highly dependent on fossil fuels for energy production. The constraints for large scale biomass energy production in Malaysia are the lack of financing for such projects, the need for large investments, and the limited research and development activities in the sector of efficient biomass energy production. The relatively low cost of energy in Malaysia, through the provision of subsidy, also restricts the potential utilization of biomass for energy production. In order to fully realize the potential of biomass energy in Malaysia, the environmental cost must be factored into the cost of energy production.